THE DIFFERENCE OF SPEI AND SPI IN DROUGHT ANALYSIS IN WEST JAVA - Arikani, Hernanti
Drought can be caused by various things, such as diminishing water catchment areas and minimal rainfall. The level of drought can be measured through the drought index. The topography differences of the West Java region cause a difference in average temperature, which is the difference input between SPEI and SPI This study aims to the differences between SPI and SPEI as meteorological drought indexes in parts of West Java. The study began by calculating the SPEI and SPI values for each location. After that the calculation is based on elevation and climate classification and comparison with the drought data from BNPB. Based on this study, SPEI indicates a greater number of drought events than SPI on a time scale of 1 and 3 months. The two drought indexes were also analyzed with altitude and temperature. In the lowlands, SPI indicates a higher level of drought than SPEI. While in the highlands and mediumlands, the results of analysis through SPI and SPEI tend to be the same. Thus, SPEI can be an alternative to SPI as a meteorological drought index in analyzing drought in Indonesia.